2017
DOI: 10.1016/j.optom.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Spherical subjective refraction with a novel 3D virtual reality based system

Abstract: PurposeTo conduct a clinical validation of a virtual reality-based experimental system that is able to assess the spherical subjective refraction simplifying the methodology of ocular refraction.MethodsFor the agreement assessment, spherical refraction measurements were obtained from 104 eyes of 52 subjects using three different methods: subjectively with the experimental prototype (Subj.E) and the classical subjective refraction (Subj.C); and objectively with the WAM-5500 autorefractor (WAM). To evaluate prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 25 publications
2
35
1
1
Order By: Relevance
“… 14 , 24 – 29 Analogously, the reproducibility of subjective refraction has been shown between ±0.39 D and ±0.55 D for the spherical equivalent. 19 , 25 , 27 , 30 32 Rosenfield and Chiu 26 suggested a limit of 0.50 D as a minimum significant shift in refractive status, which is reasonable considering the results from all the previous studies of precision in subjective refraction.…”
Section: Discussionsupporting
confidence: 67%
“… 14 , 24 – 29 Analogously, the reproducibility of subjective refraction has been shown between ±0.39 D and ±0.55 D for the spherical equivalent. 19 , 25 , 27 , 30 32 Rosenfield and Chiu 26 suggested a limit of 0.50 D as a minimum significant shift in refractive status, which is reasonable considering the results from all the previous studies of precision in subjective refraction.…”
Section: Discussionsupporting
confidence: 67%
“…However, this could not be considered clinically relevant because the differences in VAS scores were approximately 3% to 4%. In addition, Pujol et al, 22 who designed an instrument to perform objective and subjective refraction, did not report visual acuity results. No studies evaluating visual satisfaction with refractors in a quantitative manner were found in the scientific literature.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the objective and subjective refraction in the same device, Pujol et al 22 designed a new system that included an open-field wavefront-based refractor. Subjective refraction was performed based on LOA in a virtual reality environment.…”
Section: Introductionmentioning
confidence: 99%
“…They reported ICC’s regarding the repeatability for the spherical refraction of the autorefractor of 0.999 and 0.998 for the aberrometer. Comparing the intra-observer reliability of the SE obtained with classical trial frame refraction and autorefraction (using the WAM-5500, Grand Seiko Co. Ltd), Pujol [ 23 ] reported ICCs for the SE regarding the intra-observer reliability, when refractive errors were measured in 104 eyes of 52 subjects. In case of trial frame refraction, ICC was 0.993, while it was 0.991 for the used autorefractor (WAM-5500, Grand Seiko Co. Ltd).…”
Section: Discussionmentioning
confidence: 99%